Prototype of Water Turbidity Monitoring Device for Sanitation Hygiene Based on Minister of Health Regulation No 2/2023 - Nandang Gunawan Tunggal Waras; Muhammad Chasien Pratama; Dudi Adi Firmansyah; Ervanggis Minggar Kusumasari (Universitas Pekalongan, 2025)
Manual water quality monitoring in accordance with Minister of Health Regulation No. 2 of 2023 is urgently needed to detect early physical, chemical, microbiological, and radioactive contamination that could potentially endanger public health.. This water certainly has certain qualities, including its turbidity level. In accordance with Ministry of Health Regulation No.2/2023, the maximum turbidity limit for sanitary water is below 3 NTU. Therefore, a device is needed that can monitor the turbidity level of water practically. The purpose of this study is to design a prototype device for monitoring the turbidity value of sanitary hygiene water in accordance with Permenkes No. 2 of 2023. This study used the Analysis, Design, Development, Implementation, and Evaluation method. This method is expected to produce a structured and systematic approach to the development and design of the prototype that will be created. The prototype design process uses a TS 300B turbidity sensor to detect turbidity, NodeMCU ESP8266 as a microcontroller and IoT, and a 128x64 I2C OLED display. The application of IoT in this prototype is based on the use of a website to display and store measurement data. Testing was conducted on the TS 300B turbidity sensor on three samples with three repetitions, compared to the standard Nephelometric Turbidity Unit (NTU) solution. The test results showed an average accuracy and precision of 99.76% and 99.72%. Currently, some of the detection device models on the market have an accuracy of between 0-200 NTU with the added feature of data connectivity, but they are relatively expensive.Therefore, in the future, the role of IoT-based technology will be further optimized, with the aim of improving the quality of life for all